2022
DOI: 10.21203/rs.3.rs-1317377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SGLT2-inhibitors modulate the Cardiac Autonomic Neuropathy and reduce the vaso-vagal syncope recurrence in patients with type 2 diabetes mellitus: the SCAN study

Abstract: Background: In patients with type 2 diabetes mellitus (T2DM) the vaso-vagal syncope (VVS) recurrence could be due to the alteration of autonomic system function, evaluated by heart rate variability (HRV), and by 123I-metaiodobenzylguanidine (123I-mIBG) myocardial scintigraphy indexes: Heart to Mediastinum ratio (H/Mlate), and Washout rate (WR). The SGLT2-I could modulate/reduce autonomic dysfunction in T2DM patients with VVS. This effect could reduce the VVS recurrence in T2DM patients. Methods: In a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The wash-out ratio difference between the SGLT2I and control groups was reported in two studies, including 651 patients ( Shimizu et al, 2020 ; Sardu et al, 2022 ). In the random-effects model ( I 2 = 93%, p = 0.0002), the two groups were not statistically different (MD 2.13; 95% −8.48, 12.75; p = 0.69) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The wash-out ratio difference between the SGLT2I and control groups was reported in two studies, including 651 patients ( Shimizu et al, 2020 ; Sardu et al, 2022 ). In the random-effects model ( I 2 = 93%, p = 0.0002), the two groups were not statistically different (MD 2.13; 95% −8.48, 12.75; p = 0.69) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 95%
“…Three of the four studies ( Shimizu et al, 2020 ; Mehta et al, 2021 ; Liao et al, 2022 ) showed a low risk of attribution bias, and one study ( Jordan et al, 2017 ) showed a high risk. The NIH quality assessment tool revealed that two studies ( Wang et al, 2019 ; Sardu et al, 2022 ) were good quality ( Figure 2 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous research revealed that sAA is among the protein biomarkers associated with new-onset of atherosclerotic cardiovascular disease [ 46 ]. Moreover, given the role of the sympathetic over-activity in potential consequences of hypertension progression [ 47 ] such as proteinuria and kidney disease [ 48 , 49 , 50 ] but also cardiac damage and future cardiovascular prognosis [ 51 , 52 , 53 ], sAA reactivity could also serve as risk indicator at later cardiovascular disease stages. Currently, salivary biomarkers, but not sAA, are increasingly employed in screening, diagnosis, and monitoring of kidney functioning [ 54 ].…”
Section: Discussionmentioning
confidence: 99%